CYP1A1 and GSTm expression of hepatocytes induced by 7,12-dimethylbenz(a)anthracene and the influence of ethanolic extract of Gynura procumbens - Iwan Hamid (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
The cytochrome P-450 (CYP) and glutathione S-transferase (GST) enzyme systems may influence the biological effects of carcinogens. As such, these enzymes may predict the developmental risk of breast cancer, as well as be potential targets for chemoprevention. The purpose of this study was to compare the expression of CYP1A1 and GST* between treatment groups. Expression of CYP1A1 and GST* was quantified in liver tissue from 18 female Sprague Dawley rats aged 40 days, which randomly divided into six treatment groups. Those are base line group (without DMBA and ethanolic extract treatment), DMBA induced cancer group, the other two groups was administrated by DMBA after treated by ethanolic extract in two different doses, 300 mg /kg BW and 750 mg/kg BW. The last two groups were given two doses of extract ethanolic only, without initiated of DMBA. The ingestion of the extractwas carried for three weeks and the ingestion of DMBA was performed twice in the third week. The expression CYP1A1 and GST was quantified by immunohistochemistry. CYP1A1 expression was significantly higher (P < 0.05) in cancer group (DMBA) as compared with other groups. On the other hand, GST expression was lower in cancer group (P < 0.05). Result of this study demonstrated that ethanolic extract leaves of G. procumbens in 300 mg/kg BW dose could inhibit CYP1A1 stronger than are other and induced GST* level. Has effect on ethanolic extract leaves of G. procumbens has ability in played role of as blocking agent in preventing initiation stage of carsinogenesis, therefore itshould be taken into account for chemopreventing agent in mammary carsinogenesis.Key words : Gynura procumbens, breast cancer, Chemopreventive, CYP1A1, GSTμ